A protein-targeted photosensitizer for highly efficient cancer therapy. (January 2023) - Shi, M.; Pan, W.; Gao, P.; Chen, Y.; Wang, K.; Li, N.; Tang, B.
Abstract: Photodynamic therapy typically employs photo-triggered photosensitizers to generate reactive oxygen species to destroy cancer cells. However, the therapeutic effect of photodynamic therapy is often limited owing to the ultrashort diffusion distance of reactive oxygen species and easy efflux of photosensitizers. Herein, we design and synthesize a protein-targeted molecular photosensitizer for highly efficient photodynamic therapy. The designed photosensitizer can covalently bind with the sulfhydryl groups of intracellular proteins to achieve the protein targeting. Under irradiated with near infrared laser, the photosensitizer was locally activated, and the produced reactive oxygen species directly destroy intracellular bioactive proteins, causing cell dysfunction and ultimately inducing cell apoptosis. Significantly, the leakage of molecular photosensitizer is effectually avoided due to the protein targeting. In vivo experimental results indicated that the effect of treatment was efficiently enhanced with the protein-targeted strategy. This work can offer new insights for designing protein-based therapeutic drugs. Graphical abstract: A novel protein-targeted near infrared photosensitizer was successfully prepared for highly efficient cancer photodynamic therapy. Under irradiated with near infrared laser, the reactive oxygen species produced by the photosensitizer directly destroys the intracellular biologically active proteins, causing cell dysfunction and finally inducing apoptosis. Image 1 Highlights: A molecular photosensitizer with protein targeting was designed. The photosensitizer could covalently bind to intracellular sulfhydryl proteins. The photosensitizer could generate reactive oxygen species in situ to induce cell apoptosis under laser irradiation. This strategy effectively shrank the distance between generated reactive oxygen species and intracellular proteins.